Using cognitive pretesting to improve the Women's Empowerment in Agriculture Index survey - Kovarik, Chiara; Malapit, Hazel J.; Sproule, Kathryn (Agricultural and Applied Economics Association, 2015)
This presentation uses the example of cognitively pretesting the revised Women's Empowerment in Agriculture Index in Uganda and Bangladesh to explore how this method was used to create a questionnaire that more accurately captures the challenging topic of women’s empowerment. In particular, it served to clarify abstract terms and conditions, simplify difficult questions, and create an appropriate way to ask about sensitive issues. Kovarik, Chiara; Malapit, Hazel; Sproule, Kathryn